KAJIAN STRATEGI BISNIS DAN TEKNOLOGI PRODUKSI BIHUN JAGUNG UNTUK MENINGKATKAN INOVASI DAN DAYA SAING PT. SUBAFOOD PANGAN JAYA - Baihaki Baihaki; Arief Daryanto; Wati Hermawati (Jurnal Manajemen & Agribisnis, 2010)
A large number of Indonesia’s population is related with the food security. One of the efforts is food diversification i.e. producing the non-rice food such as corn vermicelli. PT. Subafood Pangan Jaya located in Tangerang, is the first producer of corn vermicelli in Indonesia who started their production in 2005. The objectives of the research are (1) to analyze the internal and external condition of the company (2) to asses  the status of component and capability of the current technology used by the company and (3) to formulate the technology and business strategy. The research was conducted by two methods, namely (1) science and technological management  information system (STMIS) to determine the status of technology component (technoware, humanware, inforware and orgaware ) and technology capabilities (operative, supportive, acquisitive and innovative); (2) internal and external factors analysis to determine the business strategy. Results of  the technology component assessment shows that the current component technology status is categorized as middle technology, whereas in the future, the compony has planned to have more sophisticated one. The result of technology capabilities assesment indicates that the current technology capabilities are comparable with the similar companies in Indonesia and they plan to be the best in ASEAN. The priority of business strategies that could be implemented are (1) product development, (2) backward integration, (3) market development, (4) horizontal integration, (5) forward integration, and (6) market penetration.